PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN INFRASTRUKTUR DI DESA TOLOMBUKAN SATU KECAMATAN PASAN KABUPATEN MINAHASA TENGGARA - RORONG, FIFIE; Rares, Joyce Jacinta; ruru, Joorie Marhaen (JURNAL ADMINISTRASI PUBLIK, 2017)
Abstrac: Public participation in policy development in countries thatimplement democracy including in Indonesia is not new. Public participationis a process to provide technical opportunities and broader authority to thecommunity together to solve various problems. As a concept and practice ofdevelopment, the concept of participation recently discussed in the 1960swhen various international institutions promote participation in the practiceof planning, implementation, and evaluation of development.This research was conducted at 9 : 1 the village chief informant. 1sysop BPD, sysop LPM, 1 religious figures, and 5 members of the public. Thetechniques of data collection is done by way of interviews, observation anddocumentation. And data analysis techniques used are informationgathering, data presentation, data reduction and withdrawal of theconclusion.Keywords : public participation, development, infrastructure